Indigenous Conflict Resolution Systems and Practices: Implications for Social Relationship Development: The Case of Debre Markos Town, 2019. - YItayew M1*, Ayenew B1, Pandey D2, Almehadi N3, Pandey B4 (AlQalam Journal of Medical and Applied Sciences, 2020)
Background and Objectives: Indigenous conflict resolution mechanism is a social capital that implies the ability of social norms and customs to grasp members of a group together by effectively setting and making possible. Methods: Cross sectional study design with a snowball sampling were employed to see the implication of indigenous conflict resolution mechanism for social relationship. Results: Regarding to making relationship continuous 54% percent of the respondent responded that social cohesion is very strong in the community when they use indigenous conflict resolution. Conclusion: Governmental institutions like court should consider indigenous elder decisions for sustainable peace development. Standard and permanent registration system should be in practice to make the younger generation informed and courageous.